The heterogeneity of antibody affinity in inbred mice and its possible immunopathologic significance - Petty, R. E. (1972)
The range of relative affinity of antibody to HSA in mice from ten strains is presented. Previously reported high and low affinity strains are not exceptional. Age, sex, dose and time after immunization have little effect on relative affinity of antibody to HSA and HST. Antibodies, raised by injecting DNP-HSA or DNP-RSA, and tested by (3)H-εDNP-L-lysine, show similar interstrain differences of affinity. This excludes recognition of only a limited proportion of the diverse antigenic sites on complex protein antigens as the sole explanation of this phenomenon.